Mesoporous shell@macroporous core aluminosilicates as sustainable nanocatalysts for direct N-alkylation of amines - Sekhar, Anandakumari C. Sunil; Ashokkumar, Anumol Erumpukuthickal; Cygnet, Choorapoikayil T.; Lakshmi, Saseendranpillai Vidhya; Deepak, Francis Leonard; Vinod, Chathakudath P. (Chemnanomat, 2018)
Aluminosilicate spheres with a macroporous core and mesoporous shell (Si/Al ratio of 11) is synthesised by a sol-gel method utilizing cetyltrimethyl ammonium bromide (CTAB) as a structure directing agent in basic medium. The selective incorporation of aluminium in the silica matrix results in the formation of aluminosilicates with an overall acidity of 0.32mmol/g with interconnected pores. Direct N-alkylation reaction is a prototype of C-N bond formation reaction and meso- macroporous aluminosilicate is shown to catalyze this reaction with excellent yield. The catalyst is tested and found sustainable for five catalytic cycles even without any high temperature regeneration step.
Keywords: Aluminosilicates; macroporous; Mesoporous; N-alkylation; nanocatalysis

Mechanistic insights into near ambient pressure activity of intermetallic NiZn/TiO2 catalyst for CO2 conversion to methanol - Dongapure, Pavan; Tekawadia, Jyoti; Thundiyil, Shibin; Caha, Ihsan; Deepak, Francis Leonard; Devi, R. Nandini (ChemCatChem, 2023)
Ni-Zn pair is predicted through descriptor-based studies to be conducive for CO2 hydrogenation. In this study, NiZn (1 : 1) intermetallics supported on TiO2 is identified as a potential candidate for near ambient pressure activity. The effect of reduction temperature on the catalyst textural properties as well as on CO2 to methanol reduction are explored. Structural and microscopic studies provide clear evidence of phase evolution of NiZn alloy with increasing reduction temperatures, along with phase variations of Zn based oxides. Interface between NiZn intermetallics and ZnO nanoparticles observed at reduction temperature of 550 degrees C, seems to play a crucial role in making this system most active and selective to methanol. In addition, in-situ IR studies provide mechanistic insights and indicates the formation of methanolic species even at ambient pressure.
Keywords: CCUS; CO2; In-situ IR; Methanol; near ambient pressure